Social innovation och Kirunabo - Sanna Bergman; Bo Nilsson (Föreningen Kulturella Perspektiv, 2019)
This article is about “social innovation”, a concept and a set of methods that have had a major impact in recent years in different sectors of society and in research. With empirical examples from Kirunabo, a two-year social innovation project in the town of Kiruna, the article illustrates different meanings of social innovation and how it is applied in practice. The article also discusses how social innovation is legitimized and motivated in general, and how it could be understood in relation to general (ideological) tendencies in society. Furthermore, the article comprises a discussion of limitations and strengths with social innovation, and one conclusion is that social innovation has contributed to the strive for social sustainability in Kiruna.